STUDI KASUS SUMBER MOTIVASI SISWA BERPRESTASI AKADEMIK PADA KELAS V SDN KARTINI CIREBON - Zulfa Ameliya, Nurlaila; Nurfadhillah, Aii; Is Inaya, Salsyabila; Kusmana, Suherli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe forms of intrinsic and extrinsic motivation, learning discipline patterns, and perceptions of environmental support, as well as the dominant factors that teachers consider most influential in maintaining achievement motivation in the top 1–3 students of grade V at SDN Kartini in Cirebon City. This research uses a qualitative method in the form of a case study, involving twelve high-achieving students and four grade V teachers. Data were collected through motivation questionnaires, student interviews, and teacher interviews, then analyzed using the interactive model of Miles, Huberman, and Saldaña with a triangulation approach of sources and techniques. The results show that both intrinsic and extrinsic motivation are always present together in all students, with varying degrees of dominance. Learning discipline was found in three variants: structured-external, active learning strategy-based, and autonomous-internal, all of which are associated with consistent achievement. Data triangulation also revealed gaps between students' self-perceptions and teachers' assessments in some cases, indicating that the process of internalizing motivation is not yet fully complete at the elementary school age. Teachers identified supportive parental involvement, family learning culture, students' personal ambitions, classroom appreciation systems, and successful experiences in competitions as the key factors that help maintain students' achievement motivation.